Key regulators of sensitization and tolerance: GM-CSF, IL-10, TGF-β and the Notch signaling pathway in adjuvant-free experimental models of respiratory allergy - Guibas, G. V.; Makris, M.; Papadopoulos, N. G. (Int Rev Immunol, 2013)
Conventional experimental models of respiratory allergy have contributed greatly to our current knowledge of the pathophysiology of allergic airway diseases; nevertheless, they are contingent upon unnatural sensitization techniques, entailing adjuvant-aided intraperitoneal (i.p) administration of antigen. Currently, there is a growing appreciation of the impact of tolerance mechanics in the pathophysiology of respiratory allergy. Thus, inasmuch as adjuvants exert a robust tolerance-modifying action, a transition from the conventional method of experimental sensitization to one that is more naturally and clinically relevant becomes important. We therefore opted to survey the literature and identify agents that could interfere with sensitization mechanics following non-adjuvant-aided airway exposure of laboratory rodents to aeroallergen. GM-CSF was found to exert robust Th2-polarizing action in this setting. Conversely, IL-10 fulfilled an important, albeit not so clear-cut, tolerance-favoring role; TGF-β was also identified as a likely instigator of tolerogenesis. The role of Notch signaling in the sensitization versus tolerance dilemma appeared to be important but diverse. Collectively, these factors appeared to profoundly and diversely modulate the balance between tolerance and sensitization in naturally relevant experimental models of allergic airway disease.